2010
DOI: 10.1007/s00264-009-0943-6
|View full text |Cite
|
Sign up to set email alerts
|

Direction of hip arthroplasty dislocation in patients with femoral neck fractures

Abstract: In order to prevent hip arthroplasty dislocations, information regarding the direction of the dislocation is important for accurate implant positioning and for optimising the postoperative regimens in relation to the surgical approach used. The aim of this study was to analyse the influence of the surgical approach on the direction of the dislocation in patients treated by a hemiarthroplasty (HA) or total hip arthroplasty (THA) after a femoral neck fracture. Fracture patients have a high risk for dislocations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 35 publications
0
7
0
1
Order By: Relevance
“…Dislocation rates may be influenced by joint capsule reconstruction [10] and implant positioning [13]. Increased dislocation rates have also been found in patients after prolonged operative time [14].…”
Section: Dorsal Vs Transgluteal Approach: From the Frying Pan Into Thmentioning
confidence: 99%
See 1 more Smart Citation
“…Dislocation rates may be influenced by joint capsule reconstruction [10] and implant positioning [13]. Increased dislocation rates have also been found in patients after prolonged operative time [14].…”
Section: Dorsal Vs Transgluteal Approach: From the Frying Pan Into Thmentioning
confidence: 99%
“…Following THA several studies showed a lower dislocation rate after the transgluteal approach compared to the dorsal approach [10][11][12][13][14]. Unfortunately most publications focus only on dislocation rate.…”
Section: Introductionmentioning
confidence: 99%
“…A basic prerequisite is exact alignment of stem and cup [1,3,7,11]. The malposition of one or both components can cause dislocation, impingement, wear and aseptic loosening [1-3, 7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…Related to the approach, different parts of the hip capsule and capsule ligaments were dissected and either left open or reconstructed, initiating an extensive discussion of the role of capsular reconstruction, where capsular reconstruction seems to be beneficial [ 7 ]. In addition, it was shown that the surgical approach predicts the dislocation direction of the hip prosthesis [ 41 ]. Thus, the whole hip capsule ligaments might be involved in reducing dislocation events.…”
Section: Discussionmentioning
confidence: 99%